Efficient continuous wave second harmonic generation of 872 nm diode laser radiation using KNbO3 with high stability. (22nd August 2017) - Rein, Benjamin; Heck, Johanna; Walther, Thomas
Abstract: We report on a highly stable laser system at a wavelength of 436 nm for the coherent excitation of the 6 3 P 1 ↔ 7 3 S 1 transition in mercury based on efficient second harmonic generation in a potassium niobate crystal. The system delivers up to 220 mW of blue light with a peak-to-peak stability of 2.3%. This stability is achieved by setting the whole build-up cavity inside a massive and temperature stabilized aluminum block. Absolute frequency stability to 480 kHz peak-to-peak is achieved by polarization spectroscopy. With a short time linewidth of 59.9 kHz and a tunability of more than 6 GHz the system is suitable for experiments requiring coherent excitation as well as applications in spectroscopy.